Epidemiology Data of Ovarian Cancer in Dr. Cipto Mangunkusumo Hospital, Jakarta - Fransisca Noela; Kartiwa H Nuryanto (Indonesian Socety of Obstetrics and Gynecology, 2016)
Objective: To describe the incidence of ovarian cancer and its characteristic in Dr. Cipto Mangunkusumo Hospital in the last 5 years. Method: This was cross sectional study design. The data was collected from Gynecology Oncology Division Cancer Registry and Dr. Cipto Mangunkusumo Hospital medical record from January 2009 to December 2013; follow up was performed to know the 4-years survival rate. Result: There were 98 subjects in this study. The majority incidence of ovarian cancer was 45-54 years old (33.6%); the incidence of ovarian cancer decreased with the increased number of parity; the majority histotype was epithelial (76.5%); and most of them were diagnosed on advanced stage (55.1%). The 4-year survival rate for epithelial type was 77%; germinal type was 83.3%; and stromal type was 100%. Based on therapy, the 4-year survival rate was 84.1% for surgical only; 83.3% in adjuvant chemotherapy group; and 68.4% in neoadjuvant chemotherapy. In the group of adjuvant chemotherapy, there was 63% patients with complete response and 41.2% patients with complete response in neoadjuvant chemotherapy. Conclusion: The highest incidence of ovarian cancer in Dr. Cipto Mangunkusumo Hospital belongs to the age of reproductive women (â‰¤ 55 years old) with the highest incidence occurs in nulliparity women. Most of the ovarian cancer cases are diagnosed in advanced stage (stage III-IV). [Indones J Obstet Gynecol 2016; 4-2: 101-106] Keywords: age, histotype, ovarian cancer, parity, response, stage, survival, treatment